Commercially Fabricated Printed Circuit Board Sensing Electrodes for Biomarker Electrochemical Detection: The Importance of Electrode Surface Characteristics in Sensor Performance - Gorachand Dutta; Anna Regoutz; Despina Moschou (Proceedings, 2018)
Here we report the first PCB-implemented electrochemical glucose biosensor using covalently immobilized glucose oxidase (GOx) on the commercially fabricated PCB electrode surface, taking particular care on the electrode surface characteristics and their effect on sensor performance. Based on the results, this assay exhibits a highly linear response from 500 μM to 20 mM (R = 0.9961) and a lower limit of detection of 500 μM.